THE LEXICAL-SEMANTIC FEATURES OF TERMS RELATING TO FOOTBAL IN UZBEK AND ENGLISH LANGUAGES (Conferencea, 2023)
This article explains about the specific aspects of terminology related to football lexemes, the lexical-semantic features of these lexemes, analyzed and compared them in English and Uzbek languages, and also accounting for theoretical knowledge about terms.